Мефодий Буслаев. Карта Хаоса: повесть / Дмитрий Емец - Емец Дмитрий Александрович (Мефодий Буслаев, 2008)
Экземпляры: ф. 1 (20110315) / Инвентарный номер: 96943 / Цена: 150.00 / Авт.знак: Е 60 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6